2020
DOI: 10.3389/fcell.2020.00223
|View full text |Cite
|
Sign up to set email alerts
|

FGF2, an Immunomodulatory Factor in Asthma and Chronic Obstructive Pulmonary Disease (COPD)

Abstract: The fibroblast growth factor 2 (FGF2) is a potent mitogenic factor belonging to the FGF family. It plays a role in airway remodeling associated with chronic inflammatory airway diseases, including asthma and chronic obstructive pulmonary disease (COPD). Recently, research interest has been raised in the immunomodulatory function of FGF2 in asthma and COPD, through its involvement in not only the regulation of inflammatory cells but also its participation as a mediator between immune cells and airway structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 127 publications
(166 reference statements)
0
26
0
Order By: Relevance
“…Although all molecular locations have distinct and important functions in cellular processes, we can see that extracellular molecules act more negatively in skin wound healing when silenced ( Figure 6 ), probably because they act as signals for several important metabolic pathways. In addition, some molecules that have different locations may do different functions depending on their location and not participate in repair-related metabolic pathways, for example, bFGF in the extracellular space acts on metabolic pathways that result in cell proliferation, migration, differentiation, and apoptosis, while in the intracellular environment, this molecule acts on antiviral immunity [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although all molecular locations have distinct and important functions in cellular processes, we can see that extracellular molecules act more negatively in skin wound healing when silenced ( Figure 6 ), probably because they act as signals for several important metabolic pathways. In addition, some molecules that have different locations may do different functions depending on their location and not participate in repair-related metabolic pathways, for example, bFGF in the extracellular space acts on metabolic pathways that result in cell proliferation, migration, differentiation, and apoptosis, while in the intracellular environment, this molecule acts on antiviral immunity [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fgf2 expression was detected in macrophages and T-cells, both players in acute and chronic inflammation (Song et al, 2015;Shao et al, 2017). Several human studies revealed that FGF2 blood level is increased in Crohn's disease and ulcerative colitis patients (Kanazawa et al, 2001) and that FGF2 could induce the expression of several proinflammatory genes in asthma (Tan et al, 2020). In inflammatory bowel disease (IBD) pathogenesis, the role of the inflammatory cytokines and the cells that produce them, T-helper1 and regulatory T-cells (specifically γδ T-cells), are well recognized.…”
Section: Fgf2 and Inflammationmentioning
confidence: 99%
“…Other studies dealing with lung diseases suggest that FGF2 may be associated with airway inflammation, bringing up the possibility of FGF2-targeted therapy. A recent review summarized the role of FGF2 as an immunomodulatory factor in COPD and severe asthma (Tan et al, 2020). In lung diseases, the inflammatory component is often responsible for the exacerbation of the pathology.…”
Section: Fgf2 and Inflammationmentioning
confidence: 99%
“…Another example of ECM bound factor is fibroblast growth factor (FGF)-2, which binds on a nanomolar level to HS ( Ibrahimi et al, 2004 ). This GAG-growth factor complex increases the binding to the FGF receptor 1 and is crucial for adequate cell signaling ( Yayon et al, 1991 ) and may be immunomodulatory factor in COPD ( Tan et al, 2020 ). Therefore, the ECM and growth factor complexes works to fine-tune cell responses and control timing, making it an important target in the development of therapies in chronic lung diseases.…”
Section: The Intrinsic Properties Of the Lung-ecmmentioning
confidence: 99%